TEN YEARS (2010 – 2020) OF EXCITING MISSIOLOGY IN SOUTH AFRICA: TRENDS AND TRAJECTORIES - Mangayi, Lukwikilu (Credo) (Scriptura, 2020)
Missiology as a theological discipline is dynamic and forever evolving. This dynamism can be observed through trends and trajectories in biblical, theological, and contextual hermeneutics. The authors of this article, by means of literature analysis, scrutinise contributions of some retiring and retired South African missiologists to unearth trends and trajectories in biblical, missiological, and contextual hermeneutics prevalent in South Africa. The authors used the data analysis programme Atlas.ti with a focus on the current four pertinent questions in missiology: What is mission? How should we do mission? What are the goals of mission? What are the contextual issues of mission today and in the near future? The findings reveal interesting trends and trajectories, and points of divergence and similarities, and because of the dynamic nature of missiology, current emerging and established missiologists should continue to shape the future trends and trajectories.